Struggling to Meet Expectations: Speaking Difficulties and Strategies of EFL Students at Datokarama State Islamic University Palu - Afifah, Afifah (Datokarama English Education Journal, 2025)
This qualitative research employs a case study design to investigate the difficulties and strategies in speaking English encountered by third-semester students of the English Tadris Department at Datokarama State Islamic University, Palu. The participants were 30 students, and data were collected through classroom observation and semi-structured interviews. The findings categorize students’ difficulties into psychological and linguistic factors. Psychologically, students experienced nervousness, fear of making mistakes, fear of judgment, and avoidance of eye contact. Linguistically, difficulties included limited fluency, a limited vocabulary, and errors in pronunciation and grammar. To overcome these barriers, students employed various strategies such as watching English movies, listening to songs, singing along, constructing sentences with new vocabulary, using gestures for visualization, and joining English clubs. Notably, students also utilized digital tools and smartphone applications, including AI, Duolingo, Elsa Speak, Let Me Speak, HelloTalk, TikTok, Instagram, and YouTube. This research highlights the struggles of English majors and provides insights for lecturers to improve teaching strategies and foster a more supportive learning environment.